Pengembangan Komponen Tujuan Kurikulum Pendidikan Agama Islam (PAI) Multikultural di Pondok Pesantren - Busthomi, Yazidul; Wahyuni , Sri (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Pondok Pesantren Raudlatul Ulum is the largest salaf Islamic boarding school in Ganjaran Village, Malang, which has an educational focus on divinity, in line with the values of Pancasila, science, and technology. This study develops the objectives of a multicultural Islamic religious education curriculum using five main principles: relevance, flexibility, continuity, efficiency, and effectiveness. This approach is based on five foundations: Salafi essential perennials, mazhabi essential perennials, modernist typology, contextual essential perennials, and tauhid-based social reconstruction. The research method used is descriptive analysis with a qualitative approach. The findings show that the developed curriculum effectively creates an inclusive learning environment oriented towards multicultural values.